Adolescent sleep and school performance — the problem of sleepy teenagers. Issue 15 (June 2020) - Sharman, Rachel; Illingworth, Gaby
Abstract : It is recommended that adolescents achieve 8–10 hours of sleep per night but a large proportion of adolescents worldwide are not achieving that amount. Adolescence is a time when the circadian clock drifts later, there are changes to the sleep homeostatic mechanisms, and individuals experience growing autonomy where poorer sleep hygiene behaviours can take hold. These changes to adolescent sleep drive bedtimes later and, with a consistent school start time, condense the opportunity for sleep. Sleep is essential for memory and learning and the shortening of sleep and subsequent sleepiness may impair an adolescent's opportunity to perform to the best of their ability in class. Numerous research groups and organisations are now striving to find ways to improve adolescent sleep including delaying school start times, providing sleep education, and utilising light therapy as a means to improve the health, wellbeing and academic performance of sleepy teenagers.